RESHUFFLE KABINET PEMERINTAHAN JOKOWI DAN DILEMA SISTEM PRESIDENSIAL INDONESIA - Annisah Putri; Maghfira Faraidiany; Iqbal Ahmady (Journal of Political Sphere, 2022)
A cabinet reshuffle is the prerogative of the president and is commonplace in a democracy like Indonesia. Under certain conditions, a cabinet reshuffle is necessary so that the performance of an organization or institution continues to run well. Usually, a cabinet reshuffle is carried out as an alternative effort to improve governance as well as a solution to improve performance constraints that occur within the cabinet. However, the shadows of past trauma cannot be separated, the public still interprets the existence of political interests in the cabinet reshuffle which is associated with the subjective issue of the distribution of political power. Not infrequently, cabinet reshuffles are seen as a means to accommodate power-sharing for coalitions of political parties. This study aims to analyze the phenomenon of cabinet reshuffle by using the concept of the presidential system in Indonesia as its main axis. In this study, the authors use the concept of a presidential regime as an important study to analyze the phenomenon of ministerial reshuffle in Indonesia. This study uses a descriptive qualitative method with secondary data sources. Collecting data using library research methods. Based on the results of a comparison of the opinions of experts and academics, it shows that a cabinet reshuffle is a natural thing, an evaluation step for improvement which is expected to increase the government's effectiveness in overcoming various government problems. country. Ministry policies resulting from the reorganization must also be able to emphasize priority scales to ensure the smooth running of work programs. Monitoring and evaluating the performance of all government agencies is also needed to improve performance in order to increase the accountability of state administration.